2013
DOI: 10.1002/chem.201303122
|View full text |Cite
|
Sign up to set email alerts
|

Increased Halide Recognition Strength by Enhanced Intercomponent Preorganisation in Triazolium Containing [2]Rotaxanes

Abstract: Three triazolium-based [2]rotaxanes containing different sized axle and macrocycle components were synthesised in good yields (40-57%) through chloride anion templation. The anion recognition properties of the interlocked receptor systems were investigated using (1)H NMR titration experiments: all three rotaxanes display impressive selectivities for halide anions over the more basic oxoanion acetate. The rotaxanes incorporating shorter, more rigid axle components with aryl-substituted triazolium groups display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…A comparison with the association constant values reported previously for protic hydrogen‐bonding triazolium rotaxane 2⋅ PF 6 12b reveals that the incorporation of the halogen‐bonding bromotriazolium motif into the axle component of the rotaxane structure results in significant enhancement of the bromide and iodide anion binding affinities. This may be a consequence of the rotaxane’s larger bromine axle substituent forcing a conformational change that results in the binding cavity being able to accommodate a larger halide anion, as illustrated in the solid‐state structure (Figure 5).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…A comparison with the association constant values reported previously for protic hydrogen‐bonding triazolium rotaxane 2⋅ PF 6 12b reveals that the incorporation of the halogen‐bonding bromotriazolium motif into the axle component of the rotaxane structure results in significant enhancement of the bromide and iodide anion binding affinities. This may be a consequence of the rotaxane’s larger bromine axle substituent forcing a conformational change that results in the binding cavity being able to accommodate a larger halide anion, as illustrated in the solid‐state structure (Figure 5).…”
Section: Resultsmentioning
confidence: 58%
“…Crucially, the incorporation of this halogen‐bond‐donating group enhanced the strength of bromide anion complexation by over two orders of magnitude, in 1:1 CDCl 3 /CD 3 OD, compared with the protic triazolium rotaxane analogue 2⋅ PF 6 (Figure 1). 12 We also recently demonstrated that the anion‐binding capabilities of triazolium rotaxane 2⋅ PF 6 could be significantly augmented by increasing the degree of inter‐component preorganisation in the rotaxane 12b. Removal of the flexible propylene linker adjacent to the triazolium group in the axle component, to form rotaxane 4⋅ PF 6 (Figure 1), resulted in a near three‐fold increase in chloride binding affinity in 1:1 CDCl 3 /CD 3 OD as a result of 4⋅ PF 6 being a more preorganised host.…”
Section: Introductionmentioning
confidence: 97%
“…[37] Interestingly,t he halide anions are bound with comparable affinity to nitrate in the order Br À > Cl À > I À .S ignificantly,t his bromide halide preference is also observed in an umber of relatedt riazolium-axle- containing rotaxane host systems. [23][24][25] It is noteworthy that the associationc onstant for nitrate with rotaxane 11·2 PF 6 (1010 m À1 )i sl arger than the association constants determined for nitrate binding by our previously reported interlocked hosts (430 m À1 and 250 m À1 for the rotaxane [21] and catenane receptors, [22] respectively) in the same competitive organicaqueous solvent mixture. This may in part reflect the increased positive charge of the bis(triazolium)acridine axle component of 11·2 PF 6 compared with the previous mono-cationic pyridinium-containing interlocked hosts.…”
Section: Anion-recognition Properties Of the [2]rotaxanementioning
confidence: 59%
“…Herein, we report the synthesis of an ovel [2]rotaxane host containing ab is(triazolium)acridine axle, which exhibits enhanced nitrate recognition in ac ompetitive organic-aqueous solventm ixture, with excellent selectivity over ar ange of more basic oxoanions (AcO À ,H CO 3 À and H 2 PO 4 À ). The nitrate anion is bound within ac omplementary three-dimensional, trigonal cavity through convergent charge-assisted triazolium CÀHh ydrogen bonds [23][24][25] donated from the acridine axle component and amide NÀHh ydrogen bonds from the macrocycle (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The rhenium(I) bipyridyl macrocycle precursor 5 was prepared using the stepwise procedure shown in Scheme 1. The allyl-appended amine 1 [15] was converted into the azide derivative 2 using the hydrogensulfate salt of imidazole sulfonylazide in the presence of K 2 CO 3 and a catalytic amount of CuSO 4 ·5 H 2 O [16] in 77 % yield. Reaction of two equivalents of 2 with 4,4'-diethynyl-2,2'-bipyridine (3) in the presence of Cu(ClO 4 ) 2 ·6 H 2 O, NaI, DBU, and TBTA, [17] gave bis(iodotriazole) bipyridyl compound 4 in 80 % yield.…”
mentioning
confidence: 99%